2020
DOI: 10.1080/21556660.2020.1734009
|View full text |Cite
|
Sign up to set email alerts
|

Autologous conditioned serum: clinical and functional results using a novel disease modifying agent for the management of knee osteoarthritis

Abstract: Objective: The purpose of this study was to investigate the potential ability of autologous conditioned serum (ACS) to decrease pain and improve joint functionality in patients affected by knee osteoarthritis (OA). Methods: Fifteen patients with clinical and radiological signs of OA of the knee were recruited for this study. Each patient received 4 injections of ACS (Orthokine; orthogen, Dusseldorf, Germany) at the site of OA once per week for 4 weeks. Clinical and functional evaluation was performed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Overall, the present study indicates and confirms that ACS is a safe and effective treatment for knee OA; 9,16,17 particularly, it is able to rescue a good proportion of patients from orthopaedic surgery, once medical and PRP treatments have failed. On the other hand, to widen these results to the general population of patients with knee OA, as well as to replace PRP treatment with ACS after failure of standard medical interventions, larger controlled studies are required to confirm our encouraging data and to determine whether ACS may be a standard of treatment when current medical treatments fail.…”
Section: Discussionsupporting
confidence: 76%
“…Overall, the present study indicates and confirms that ACS is a safe and effective treatment for knee OA; 9,16,17 particularly, it is able to rescue a good proportion of patients from orthopaedic surgery, once medical and PRP treatments have failed. On the other hand, to widen these results to the general population of patients with knee OA, as well as to replace PRP treatment with ACS after failure of standard medical interventions, larger controlled studies are required to confirm our encouraging data and to determine whether ACS may be a standard of treatment when current medical treatments fail.…”
Section: Discussionsupporting
confidence: 76%
“…Their study as others mentioned above revealed significant improvement in both clinical and functional scales after the intervention. Despite few adverse effects (pain and swelling and one case of joint rigidity after injection), the authors suggested ACS as a safe and tolerable as well as effective therapeutic intervention for knee OA [ 31 ]. In another research conducted in Egypt, Fathalla et al investigated the effectiveness of IA ACS in 30 patients with knee OA (KL grade I–III) and reported significant improvement in all WOMAC scores, which persisted until the third month of follow up [ 32 ].…”
Section: Joint Disordersmentioning
confidence: 99%
“…Likewise, Orthokine® uses a special syringe containing CrSO4-treated grade glass beads in order to promote IL-1Ra synthesis and accumulation (currently marketed as Orthogen® AG, Düsseldorf, Germany). 15 , 38 …”
Section: The Blood-derived Product Familymentioning
confidence: 99%
“…12,13 Furthermore, novel blood-derived products specific for OA are emerging. 14,15 However, clinical response varies enormously between patients, probably because OA involves different etiologies and pathogenic mechanisms, and thus an array of mixed phenotypes. Which patients are the best candidates for blood-derived therapies thus remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%